E-COMMERCE SEBAGAI MEDIA PROMOSI MENINGKATKAN VOLUME PENJUALAN PADA APLIKASI SHOPEE DALAM PANDANGAN EKONOMI SYARIAH - Safitri, Kurniawati (Gapenas Publisher, 2024)
The evolution of the internet has touched various sectors, one of which is sales carried out online. Shopee is one of the most popular electronic commerce sites in Indonesia. This article aims to answer the question of using the Shopee application as a promotional tool to increase sales from the seller's perspective with a sharia economic view. The data collection method used is by collecting data from previous research. The results indicate that Shopee can be used as a promotional medium to encourage increased product sales. This factor comes from the effectiveness of the features available on Shopee, which support sellers in carrying out promotions so that sales can increase. Meanwhile, Islam views trading using online methods as a legitimate activity and by Islamic teachings if it meets the principles of divinity, justice, consent, expediency, honesty, freedom, and ethics in Islamic business